2014
DOI: 10.1179/1607845414y.0000000212
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 plays a crucial role in chemoresistance in acute myeloid leukemia

Abstract: The drug-resistant AML cell line HL-60R was significantly less sensitive to cytarabine and daunorubicin than HL-60 cells. HO-1 mRNA and proteins were highly expressed in HL-60R cells. However, down-regulating HO-1 significantly enhanced the sensitivity of HL-60R to chemotherapy, and the expressions of HIF-1ɑ and GLUT1 mRNA and proteins decreased. Meanwhile, the expressions of caspase-3 and caspase-8 proteins increased, while that of bcl-2 decreased. Overexpressions of HO-1, HIF-1ɑ, and GLUT1 were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…The drug-resistant acute myeloid leukemia (AML) cell line HL-60R is significantly less sensitive to cytarabine and daunorubicin than HL-60 cells and this correlates to HO-1 overexpression. Indeed, HO-1 downregulation significantly enhanced the sensitivity of HL-60R to chemotherapy [97]. Moreover, in the majority of AML patients, especially in those with acute monocytic leukemia and leukocytosis, HO-1 is aberrantly overexpressed.…”
Section: Ho-1 In Cancer Growth and Resistance To Therapymentioning
confidence: 99%
“…The drug-resistant acute myeloid leukemia (AML) cell line HL-60R is significantly less sensitive to cytarabine and daunorubicin than HL-60 cells and this correlates to HO-1 overexpression. Indeed, HO-1 downregulation significantly enhanced the sensitivity of HL-60R to chemotherapy [97]. Moreover, in the majority of AML patients, especially in those with acute monocytic leukemia and leukocytosis, HO-1 is aberrantly overexpressed.…”
Section: Ho-1 In Cancer Growth and Resistance To Therapymentioning
confidence: 99%
“…Cancer cells maintain a balance of ROS by activation of oxidative stress response genes, many of which are regulated by the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) [22, 23]. The increased expression of oxidative stress response genes contributes to cancer cell resistance to chemotherapies such as anthracyclines [24, 25], which work in part by inducing oxidative stress. Given the significant protection that adipocytes provide to ALL cells, particularly against the anthracycline daunorubicin (DNR) [16], we investigated whether adipocytes protect ALL cells from chemotherapies by relieving oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, studies have suggested that chemotherapy resistance is the main reason for the failure of chemotherapy and disease recurrence for AML patients. [4][5] The bone marrow microenvironment plays a critical role in the development, progression, and relapse of AML. 6 Haematopoietic stem cells (HSCs) and leukemia-initiating cells (LICs) reside in a hypoxic bone marrow niche.…”
Section: Introductionmentioning
confidence: 99%